2021
DOI: 10.1101/2021.12.16.472987
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disrupting ATXN1 Nuclear Localization in a Knock-in SCA1 Mouse Model Improves a Spectrum of SCA1-Like Phenotypes and their Brain Region Associated Transcriptomic Profiles

Abstract: SUMMARYSpinocerebellar ataxia type 1 (SCA1) is a dominant trinucleotide repeat neurodegenerative disease characterized by motor dysfunction, cognitive impairment, and premature death. Degeneration of cerebellar Purkinje cells is a frequent and prominent pathological feature of SCA1. We previously showed that transport of ATXN1 to Purkinje cell nuclei is required for pathology, where mutant ATXN1 alters transcription. To examine the role of ATXN1 nuclear localization broadly in SCA1-like disease pathogenesis, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Notably, deletion of f-ATXN1 146Q from muscle substantially reduced kyphosis that in mice is associated with paraspinal skeletal muscle atrophy 18 as well as restored normal dorsiflexor strength, muscle mass and fiber size. As seen for other SCA1-like phenotypes, motor dysfunction, cognitive deficits, and premature lethality 20 , proper nuclear localization of expanded ATXN1 was shown to be critical for muscle pathogenesis. These results show that f-ATXN1 146Q/2Q along with f-ATXN1 146Q/2Q ; Acta1-Cre will provide an excellent experimental platform for elucidating the molecular aspects of ATXN1[146Q]-induced muscle pathogenesis.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Notably, deletion of f-ATXN1 146Q from muscle substantially reduced kyphosis that in mice is associated with paraspinal skeletal muscle atrophy 18 as well as restored normal dorsiflexor strength, muscle mass and fiber size. As seen for other SCA1-like phenotypes, motor dysfunction, cognitive deficits, and premature lethality 20 , proper nuclear localization of expanded ATXN1 was shown to be critical for muscle pathogenesis. These results show that f-ATXN1 146Q/2Q along with f-ATXN1 146Q/2Q ; Acta1-Cre will provide an excellent experimental platform for elucidating the molecular aspects of ATXN1[146Q]-induced muscle pathogenesis.…”
Section: Discussionmentioning
confidence: 77%
“…Recently, we found that proper nuclear localization of mutant ATXN1 is critical for many disease-like phenotypes including motor dysfunction, cognitive deficits, and premature lethality 20 . Like f-ATXN1 146Q/2Q mice, we observed smaller dorsiflexor muscle mass (Fig.…”
Section: Deletion Of the F-atxn1mentioning
confidence: 99%